Application of Intraoperative Ultrasound in Robot-assisted Thrombectomy for Renal Cell Carcinoma - Zhu Jianing, Li Nan, Luo Yukun, Li Qiuyang (Advanced Ultrasound in Diagnosis and Therapy)
Preoperative imaging is crucial for patients diagnosed with renal cell carcinoma presenting with thrombus. These individuals frequently exhibit a hypercoagulable state, raising the risk of thrombus progression or the formation of a new bland thrombus post-imaging and pre-surgery. Intraoperative ultrasound, employed under direct visualization, offers real-time, dynamic detection of thrombi, potentially influencing surgical decisions. This short review explores the utility of intraoperative ultrasound in robot-assisted thrombectomy for renal cell carcinoma, detailing its primary applications and added value in mitigating surgical risks for urologists.